(untitled) (Journal of the Bangladesh Agricultural University, 2020)
The present study was carried out to evaluate the effect of sire and environment on growth performance of grade-2 Brahman calves. A total of 70 grade-2 Brahman calves produced from 6 sires (14BR0043, 7BR-524, 14BR0040, 7BR-527, 14BR0041,7BR-522) were included in this study to know the effect of different sires on calves growth performances those located on 8 different areas (Barisal, Chattogram, Dhaka, Khulna, Mymensingh, Rajshahi, Rangpur, Sylhet). Analyses were performed by using Statistical Analysis System (SAS) version 9.1.3. Analyses revealed that sires had significant effect (p<0.05) on 1-month, 6-month, 24-month weights and average daily gain. In contrast, non-significant effect (p>0.05) was observed on birth weight, 3-month, 9-month and 12-month weights of progeny. The highest mean birth weight (32.27±0.59 kg) and 1-month weight (57.58±2.11 kg) of calves was found from the sire 14BR0040 and 14BR0041, respectively. The highest mean of 3-month (81.57±3.13 kg), 6-month (186.71±6.20 kg), 9-month (332.43±8.07 kg), 12-month (463.57±13.61 kg) and 24-month (903.33±16.71 kg) weights were found by sire 7BR-524, 14BR0043, 14BR0043, 7BR-524 and 14BR0040, respectively. The area significantly (p<0.01) affected on 3-month and 6-month weight of calves. The highest 3-month weight (90.00±7.52 kg) and 6-month weight (184.06±3.79 kg) of calves were recorded in Barisal and Rangpur, respectively. The average daily gain (ADG) of progeny from birth to 6-months had been significantly (p<0.01) influenced by different areas. The strong positive correlation between ADG from 12 to 24 months and ADG from 0 to 24 months was 0.91. This result showed that the sire and environment had significant effect on above growth traits at different ages of Brahman progeny, which indicated that best sire in best environment can produce superior progeny. As Brahman breed are good meat producer and the average daily gain is quite satisfactory in the specific location so it is concluded that Brahman breed can be a valuable alternative approach for increasing meat production. However, further study with large sample size of grade-2 Brahman should be taken to increase beef production. J Bangladesh Agril Univ 18(2): 456–462, 2020 https://doi.org/10.5455/JBAU.73449